Visual dependency and postural control on swing performance in golf players - Micarelli, A.; Viziano, A.; Lanzillotta, A.; Ruscello, B.; D`Ottavio, S.; Alessandrini, M. (European Journal of Sport Science, 2019)
Individuals have to reweight the respective contribution of the different sources of sensorial information for regulating posture and balance, especially during fine task execution. Given the evidences indicating strategy during swing performance as associated with prioritization of task-relevant visuospatial information for skill execution, the aim of the present work is to assess differences in visual dependency (VD) and postural control in a population of expert (EXP) and non-expert (NEXP) golfers when compared with healthy subjects (HC) and to discover possible relationships between these outcomes and swing performance. Thus, 15 golfers (EXP = 7; NEXP = 8) and 32 matched HC underwent otoneurological testing including video Head Impulse Test, posturography and Rod and Disk Test (RDT). Golf players also underwent a swing session procedure, which performance was measured by means of the Flightscope X2 Doppler-radar launch monitor system. EXP subjects demonstrated significant (p < 0.05) lower values in i) counter-clockwise (CCW) and clockwise (CW) dynamic conditions when compared with both NEXP and HC subjects RDT outcome measures and ii) surface and length posturography values as compared with HC subjects. When treating golf players outcomes as `a continuum`, CCW and CW scores were found to positively correlate with both lateral distance and horizontal launch angle and to negatively correlate with spin rpm. In conclusion, the present study suggests that the high-level of visual-independency demonstrated by EXP subjects may be functionally related in expert golfers to an effective motor strategy preferentially not referring to an inappropriate reliance on visual input.